Pengaruh Usia dan Tingkat Pendapatan Terhadap Potensi Kecelakaan Lalu Lintas dengan Menggunakan Stuctural Equation Modeling (SEM) - Adinda Laloma; Lucia Ingrid Regina Lefrandt; Semuel Yacob Recky Rompis (Universitas Negeri Gorontalo, 2023)
Cause traffic accidents include human factors, vehicle factors, road factors and the environment. This study aims to analyze the effect of age, income level, and road geometry on the potential for traffic accidents. The research location is in the Talaud Archipelago Regency, North Sulawesi Province. This research uses a quantitative approach by collecting data using a questionnaire distributed to 200 respondents who use two-wheeled and four-wheeled vehicles. The Likert scale measurement method analysis uses the Structural Equation Modeling (SEM) on the Amos 22.00 program The results showed that age does not directly have a significant effect on the potential for accidents of 0.917 but indirectly age has a significant effect on the potential for accidents through the condition of the vehicle with a statistical value of 3.779, the level of income directly has a significant effect on the potential for accidents with a probability value <0.001 and indirectly has a significant effect through vehicle condition Z statistics value of 2.925, road geometry does not directly influence the potential for accidents with a probability value of 0.184, driving behavior does not directly influence the potential for accidents 0.820 and vehicle conditions directly have a significant effect on potential accidents probability value <0.001.